2015
DOI: 10.1088/0031-9155/60/9/3825
|View full text |Cite
|
Sign up to set email alerts
|

Relative electron density determination using a physics based parameterization of photon interactions in medical DECT

Abstract: Radiotherapy and particle therapy treatment planning require accurate knowledge of the electron density and elemental composition of the tissues in the beam path to predict the local dose deposition. We describe a method for the analysis of dual energy computed tomography (DECT) images that provides the electron densities and effective atomic numbers of tissues. The CT measurement process is modelled by system weighting functions, which apply an energy dependent weighting to the parameterization of the total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
(43 reference statements)
1
23
0
1
Order By: Relevance
“…Van Abbema et al . developed a method that is not based on calibration, but requires spectral knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Abbema et al . developed a method that is not based on calibration, but requires spectral knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, several papers were published on DECT to either show potential benefits for radiotherapy or to propose a mathematical formalism to extract tissue parameters relevant to dose calculation. Recent publications propose the extraction of ED and EAN (or alternatively, the I ‐value), from DECT images . These methods rely on postreconstruction data analysis, conversely to sinogram‐based methods (e.g., Refs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also successfully experimentally validated by Hünemohr et al, who found a mean absolute deviation of measured from reference electron densities of 0.4% for tissue substitutes. Studies of other algorithms reported similar results, without any clear advantage for one or the other method.…”
Section: Introductionmentioning
confidence: 68%
“…[8][9][10][11] Moreover, with DECT, the use of a CT number to density calibration curve is not necessary. 11,12 In therapy planning for proton irradiations, accurate knowledge of proton stopping powers is essential. Proton stopping powers can be determined from the electron density and the effec-tive atomic number.…”
Section: Introductionmentioning
confidence: 99%